PENDEKATAN PEMBELAJARAN PARAMASASTRA JAWA DI SEKOLAH DASAR - Maruti, Endang Sri (Premiere Educandum, 2014)
Learning paramasastra (grammar), especially paramasastra Java, in the SBC between two poles. On the one hand, learning grammar is important to determine how the students understanding of the Java language, on the other hand grammar learning integrable in four aspects already existing skills in the curriculum. Determination of the polemical stance in the face of an important thing to do, so that the teacher can determine the approach to be used in learning.Keywords: approach, learning, paramasastra, the Java language